Komi can't communicate. Volume 16 - Oda, Tomohito, 1991-; Werry, John (Translator) (VIZ Media, LLC, 2021)
"It's the day of the sports festival at Itan High and the students are brimming with competitive spirit! But when Tadano forgets his lunch, his classmates put aside their rivalries and team up to make sure he gets full. Can Komi and Manbagi work up the courage to hand-feed their crush, or will they be the only lunchtime losers?"--Back cover.